Analysis of Differences in Overburden Volume Calculation Results Based on Survey and Truck Count Method at PT Bina Sarana Sukses Job Site Manambang Muara Enim - Johanes Pauji Sihombing; Edwin Harsiga; Guskarnali Guskarnali (Journal of Geology and Exploration, 2025)
PT Bina Sarana is a coal mining contractor located in Darmo village and Pulau Panggung village. Lawang Kidul district, Muara Enim regency, South Sumatera province. The calculation of overburden volume using survey and truck count method on May is a 16,394.177 BCM, percentage 11.57. The aim of this study is to determine the volume of overburden transported based on survey and truck count method, analyze the casual factor and reparation. This study use quantitative method, overburden production on June and July is 910,304.25 BCM and truck count is 975.984,86 BCM. The identification of problem conducted sampling test to know the casual capacity of vessel, CMT 96 is 23.26 BCM, CMT 106 is 25.30 BCM on June and CMT 96 is 23.21 BCM, CMT 106 is 24.87 BCM on July. The identification of problem used improving the calculation formula truck count, percentage routinely conducted sampling test to determine the actual capacity of vessel. The factor that influence of overburden volume known with survey and truck count method along June-July of 2024 are the discrepancy between actual load, the lack of bucket fill factor, the inaccurate of field survey data (inaccurate setting, tool centering, inaccuracy of detailed progress point). After the improvement, the result of overburden volume of truck count on June-July is 924,735.17 BCM, has a decrease in company’s calculation differences of 6.72 % to 1.5 % with the company determination 2.75 %.